2019
DOI: 10.11130/jei.2019.34.4.725
|View full text |Cite
|
Sign up to set email alerts
|

External Debt, Investment, and Economic Growth: A Seemingly Unrelated Regression Model for Low-Income Countries

Abstract: This study analyzes whether external debt is a driving factor for investment and economic growth in low-income countries. Using data over the period 2000~2017, we performed an analysis using the 23 countries in the sample and a split-sample analysis wherein we separated less indebted countries (12) from more indebted countries (11). Empirical results of the seemingly unrelated regressions model indicate that external debt significantly decreases investment and economic growth for both the total sample and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
(44 reference statements)
3
25
0
1
Order By: Relevance
“…Similarly, countries who fail to meet their debt obligations suffer from severe macroeconomic imbalances in the form of high fiscal discrepancy, deterioration in foreign exchange reserves, fall in confidence of investors, instability in exchange rate and persistent fall in its credit rating by the international rating agencies (Economic Survey of Pakistan , 2007Pakistan , -2008. It means that when the fund raisers failed to inject the borrowed money in the revenue generating and other productive projects, then excessive borrowing not only leads to reduce the debt servicing and loan amortization abilities of the indebted country but also creates obstacles in the path of getting sustainable economic growth and development in the long run (Abdelaziz et al, 2019). Therefore, the borrowed money should be utilized effectively and productively in such types of developmental and investment-oriented projects which help in enhancing the debt carrying capacity of the debtor country.…”
Section: Introducti̇onmentioning
confidence: 99%
“…Similarly, countries who fail to meet their debt obligations suffer from severe macroeconomic imbalances in the form of high fiscal discrepancy, deterioration in foreign exchange reserves, fall in confidence of investors, instability in exchange rate and persistent fall in its credit rating by the international rating agencies (Economic Survey of Pakistan , 2007Pakistan , -2008. It means that when the fund raisers failed to inject the borrowed money in the revenue generating and other productive projects, then excessive borrowing not only leads to reduce the debt servicing and loan amortization abilities of the indebted country but also creates obstacles in the path of getting sustainable economic growth and development in the long run (Abdelaziz et al, 2019). Therefore, the borrowed money should be utilized effectively and productively in such types of developmental and investment-oriented projects which help in enhancing the debt carrying capacity of the debtor country.…”
Section: Introducti̇onmentioning
confidence: 99%
“…The study employed the seemingly unrelated regressions model. Abdelaziz, et al, (2019), concluded that on one hand, external debt is negatively significant to both the total sample and the subsamples. On the other hand, Foreign trade has a positive significance on growth per capita income.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…In their study, Abdelaziz, et al, (2019), analyzed the impact of external debt on investment and economic growth. The paper selected a sample of 23 lowincome countries and divided them into subsamples, (12) low indebted countries and ( 11) more indebted countries.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Using ordinary least squares method Saxena and Shanker (2018) found a negative impact of external debt on India's economic growth during 1990-91 -2015-16. Abdelaziz et al (2019) examined the impact of debt on investment and growth separately for twelve less indebted and eleven highly indebted countries using SUR method. For the split models as well as for the entire sample the results indicate a negative impact of external debt on investment and growth.…”
Section: A Brief Survey Of the Literaturementioning
confidence: 99%